Evaluation of incidence of phototherapy induced hypocalcaemia in term newborns with neonatal hyperbilirubinemia and its clinical significance: a cross sectional study with controls - Gupta, Raksha; Singh, Davinder; Yadav, Meetu; Panda, Prateek Kumar; Nagaraj, Niranjan; Bana, Sailen Kumar (International Journal of Contemporary Pediatrics, 2018)
Background: Neonatal hyperbilirubinemia in many of the cases is only in physiological range, but quite often it requires phototherapy and even exchange transfusion for proper management. Although hypocalcemia is often proposed to be associated with phototherapy in term and preterm newborns, its exact incidence and clinical significance still remains to be elucidated. Methods: Current study was carried out in a tertiary care center in North India with 29 term neonates in test group receiving single surface phototherapy and 29 age, sex and gestational age matched neonates in control group, who did not receive phototherapy. Serum calcium levels at 0 and 48 hours of starting phototherapy were determined in both the groups and compared. Results: Mean difference of Serum ionized calcium between two groups was statistically significant at 48 hours with mean for test group was 4.58 mg/dl compared to 4.94 mg/dl for control group (p <0.001). 10 newborns (47%) in test group had hypocalcemia according to standard definitions and 3 out of them (30%) had were clinically symptomatic with jitteriness and poor feeding, which resolved after calcium supplementation Conclusions: Term neonates undergoing phototherapy are at increased risk for hypocalcemia. A universal recommendation regarding calcium supplementation in neonates undergoing photherapy is yet to be established but seems like a reasonable intervention.